Practice patterns and their influence on prevalence of musculoskeletal disorders among Indian dentists - Shankar, Raghavendra; Kalappa, Sandhya (International Journal of Research in Medical Sciences, 2017)
Background: The term musculoskeletal disorders (MSDs) refers to conditions that involve the nerves, tendons, muscles and supporting structures of the body. Dentists are prone for MSDs especially neck and back pain owing to the following risk factors as a part of their practice – repetitive movements, maintenance of awkward body postures for a long time and tasks that require fine motor skills and close visual focus. Methods: 300 practicing dentists in Bangalore were asked to respond to a questionnaire about their practice pattern (years of practice, hours of work, specialization, two-handed/four handed dentistry, use of magnifications etc), their general lifestyle including exercise and fitness patterns, prevalence of MSDs and their general awareness regarding MSDs. The responses were analyzed using descriptive statistics, univariate analysis and Chi-square tests for independence. Results: In our study 95.16% (n=236) and 90.32% (n=224) respondents reported MSDs in the past and in the previous 12 months of the study respectively. 54.84% (n=136) reported at least one episode of backache, 51.61% (n=128) reported neck pain, 19.35% (n=48) reported pain in the shoulder and 32.25% (n=80) reported pain in the wrist and/or hand in the previous 12 months. Our study found significant influence of the hours of work, use of assistant and magnification on backache, neck pain and wrist/hand pain. Conclusions: Work-related pain being common and multifactorial, any possible solution should also be multifactorial and can be managed or alleviated effectively using a multifaceted approach and the strategies for prevention and care are also discussed.